Left Anterior Fascicular Block After Transcatheter Closure of Ventricular Septal Defect in Children - Wu, Zhijun; Yang, Penghui; Xiang, Ping; Ji, Xiaojuan; Tian, Jie; Li, Mi (Frontiers in Cardiovascular Medicine, 2021)
Background Arrhythmia is the most common complication after the transcatheter closure of ventricular septal defect. However, we are not clear enough about postprocedural left anterior fascicular block. This study presents the clinical characteristics, prognosis, and related risk factors of left anterior fascicular block after transcatheter closure of ventricular septal defect in children. Methods The clinical and follow-up data of the patients in the Heart Center of Children's Hospital of Chongqing Medical University from June 2009 to October 2018 were reviewed. And 30 cases were eligible of all 1371 cases. Results Electrocardiogram showed left anterior fascicular block within 3 days and the most patients gradually returned to normal within 1 to 2 years, showing a dynamic change. Left ventricular end-diastolic dimension Z score ranged -2 to 2 in all children, and no decrease of left ventricular ejection fraction was found in all children. The high ratio between ventricular septal defect size and body surface area(p<0.05, OR 2.6, 95% CI:1.136–6.113), large diameter difference between the occluder size and ventricular septal defect size (p<0.05,OR 2.1,95% CI:1.036–4.609) were independent risk factors for postprocedural left anterior fascicular block. Conclusions The incidence of postprocedural left anterior fascicular block is not that low and the overall prognosis is quite good at the current follow-up stage. No progressive severity has been found such as complete left bundle branch block, double (triple) bundle branch block and atrioventricular block to have influence on cardiac systolic and diastolic function.